PENERAPAN EDMODO UNTUK MENINGKATKAN MOTIVASI BELAJAR MAHASISWA PGSD STKIP MUHAMMADIYAH MUARA BUNGO - Tri Wiyoko; Puput Wahyu Hidayat; Iwan Setiawan (Jurnal Muara Pendidikan, 2019)
This study aims to improve student learning motivation after applying Edmodo in lectures on Basic Natural Sciences. This type of research is a pre-experimental design with the type of pretest and posttest group desing. The analysis used is descriptive quantitative. The method of data collection in the study used a learning motivation questionnaire. The subjects of this study were 28 STKIP Muhammadiyah Muara Bungo students. The results showed that there was an increase in motivation to learn by using Edmodo. Increased student learning motivation by 14.93%. Paired Samples Test test results Student learning motivation obtained tcount = 4.415 means tcount = 4.415> ttable = 2.0518 and Sig. = 0.00 <0.05. This shows that the application of Edmodo in the subject of Basic Natural Sciences has a significant influence on student learning motivation.